Storytelling as a survival strategy in patricia grace!s potiki - BAKIR, CAHİT (My University, 2023)
This paper examines the importance of storytelling in Patricia Grace’sPotikiin an attempt toresist the assimilation of Māori culture, annihilation of their language and destruction of their ancestral lands. Patricia Grace embarks on reviving Māori identity through the use of their language, their cultural symbols and their stories which, unlike the dominant Pakeha (New Zealanders of European descent) culture, stress wholeness and unity in both living and non-living matter.The Māori have a rich oral tradition, and a very important aspect of Māori culture is storytelling. Grace’s use of narrative voice thus diverges from Westernliterary conventions and has close ties to Maori oral traditions.The novel intertwines oral and written narrative throughout the text, blending the two in a way that undermines the traditional Western narrative structure and recenters the artistic, linguistic, and cultural history ofMāori.Storytelling is intrinsic to the narrative composition of the novel, and it determines the entire plot.The paper argues that Graceemploys storytelling as a means to resist the assimilation of Māori culture, colonization of their lands and create a communal Māori identity.
Keywords: Sosyal ve Beşeri Bilimler; Dil ve Edebiyat; Batı Dilleri ve Edebiyatları; İngiliz Dili ve Edebiyatı; Social Sciences and Humanities; Philology; Western Languages and Literatures; English Language and Literature; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; EDEBİYAT; EDEBİYAT, ALMAN, HOLLANDA, İSKANDİNAV; EDEBİYAT, İNGİLİZ ADALARI; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; LITERATURE; LITERATURE, GERMAN, DUTCH, SCANDINAVIAN; LITERATURE, BRITISH ISLES; Edebiyat ve Edebiyat Teorisi; Sosyal Bilimler ve Beşeri Bilimler; Literature and Literary Theory; Social Sciences & Humanities